Peran Stabilitas Emosi dalam Pengambilan Keputusan Organisasi Mahasiswa - Rusdi Hidayat; Indah Respati Kusumasari; Pinky Arisma Putri; Nindia Murdiana (Politeknik Kampar, 2024)
Decision making is a series of alternative choices of actions that have certain risks in order to achieve organizational goals through the best decisions. Selecting the best alternative after evaluating its effectiveness in achieving the decision maker's goals. The decision-making process requires a systematic approach to problems through collecting data that is processed into information, as well as considering relevant factors before deciding. Emotional stability plays an important role in decision making by student organizations.